2018
DOI: 10.1111/jgs.15476
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Implementation of the Interventions to Reduce Acute Care Transfers (INTERACT) Quality Improvement Program Associated with Number of Hospitalizations

Abstract: Increased reported use of core INTERACT tools was associated with significantly greater reductions in all-cause hospitalizations and PAHs in both intervention and control SNFs, suggesting that motivation and incentives to reduce hospitalizations were more important than the training and support provided in the trial in improving outcomes. Further research is needed to better understand the most effective strategies to motivate SNFs to implement and sustain quality improvement programs such as INTERACT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 21 publications
3
39
0
Order By: Relevance
“…The authors contend this null result could reflect the challenges of implementing a complex, resource-intensive intervention in the nursing home setting, something noted in pre-trial studies where drop-out of nursing homes was a concern 31. A subsequent per-protocol analysis found that nursing homes able to implement the intervention saw reductions in hospitalisations, but only a minority were able to do so 32. Enlisting external support to assist nursing homes with quality improvement—such as that funded by the Centers for Medicare and Medicaid Services through the Quality Improvement Organizations (QIO) programme—may be helpful, though evaluation of the effect of QIOs remains surprisingly limited 33 34…”
mentioning
confidence: 99%
“…The authors contend this null result could reflect the challenges of implementing a complex, resource-intensive intervention in the nursing home setting, something noted in pre-trial studies where drop-out of nursing homes was a concern 31. A subsequent per-protocol analysis found that nursing homes able to implement the intervention saw reductions in hospitalisations, but only a minority were able to do so 32. Enlisting external support to assist nursing homes with quality improvement—such as that funded by the Centers for Medicare and Medicaid Services through the Quality Improvement Organizations (QIO) programme—may be helpful, though evaluation of the effect of QIOs remains surprisingly limited 33 34…”
mentioning
confidence: 99%
“…Only 73 (50%) of the 145 intervention patients discharged to SNF, ALF, or home with home health went to one of the participating organizations, and their use of INTERACT was variable. In one study, increasing use of core INTERACT tools was associated with lower rates for potentially avoidable hospitalizations, although this result could also reflect facilities' motivation to reduce hospitalizations as opposed to INTERACT use itself …”
Section: Discussionmentioning
confidence: 99%
“…First, it targeted patients aged 75 years and older who were at high risk for readmission and other complications of hospitalization because focusing resources on high‐risk patients enhances the potential for cost‐effectiveness. Second, it included multiple components of previously tested interventions to address the multifactorial nature of hospital readmissions in the older adult population, and it incorporated elements of programs that have demonstrated some success in older populations, including the Care Transitions Intervention, the Transitional Care Model, and Interventions to Reduce Acute Care Transfers …”
mentioning
confidence: 99%
“…This is a secondary analysis of data from a randomized, controlled implementation trial of the Interventions to Reduce Acute Care Transfers (INTERACT) program. The main results of the trial and root cause analyses on transfers to the hospital have been reported . The Florida Atlantic University institutional review board approved the trial as a quality improvement project.…”
Section: Methodsmentioning
confidence: 99%
“…The main results of the trial and root cause analyses on transfers to the hospital have been reported. [10][11][12]31,32 The Florida Atlantic University institutional review board approved the trial as a quality improvement project. Six hundred thirteen SNFs recruited in collaboration with national organizations expressed interest in participation, 391 were screened for eligibility in online surveys and telephone interviews, and 264 eligible SNFs were randomly assigned to 1 intervention and 2 control groups.…”
mentioning
confidence: 99%